Extracellular heat shock protein 70 promotes osteogenesis of human mesenchymal stem cells through activation of the ERK signaling pathway. Issue 24 (19th November 2015) - Chen, Erman; Xue, Deting; Zhang, Wei; Lin, Feng; Pan, Zhijun
Abstract : Heat shock proteins have protective effects when cells are exposed to stress. However, the relationship between extracellular heat shock protein 70 (eHSP70) and osteogenesis of hMSCs has not been reported. The results of this study showed that HSP70 (200 ng/ml) increases alkaline phosphatase activity and promotes hMSC mineralization. Under osteogenic induction conditions, HSP70 significantly upregulated the expression of osteo‐specific genes, such as the runt family transcription factor Runx2 and osterix (OSX). Comparative expression profiling by microarray and pathway analyses revealed that HSP70 promotes osteogenesis of hMSCs through activation of the ERK signaling pathway. HSP70 may be a potential therapeutic agent for the treatment of bone nonunion. Abstract : HSP70 increases alkaline phosphatase activity and promotes hMSC mineralization. HSP70 upregulates the expression of osteo‐specific genes. HSP70 promotes osteogenesis of hMSCs through activating the ERK signaling pathway.